2020
DOI: 10.1002/soej.12475
|View full text |Cite
|
Sign up to set email alerts
|

The contagion externality of a superspreading event: The Sturgis Motorcycle Rally and COVID‐19

Abstract: Large in‐person gatherings of travelers who do not socially distance are classified as the “highest risk” for COVID‐19 spread by the Centers for Disease Control and Prevention (CDC). From August 7–16, 2020, nearly 500,000 motorcycle enthusiasts converged on Sturgis, South Dakota for its annual rally in an environment without mask‐wearing requirements or other mitigating policies. This study is the first to explore this event's public health impacts. First, using anonymized cell phone data, we document that foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…One proposed reason for the observed differences is that the Sturgis Rally was associated with lower compliance with non-pharmaceutical interventions (NPIs), such as mask wearing and physical distancing, that are associated with decreased transmission risk. Observational data showed that attendees from regions with stricter NPI mandates were associated with lower onward transmission risk than attendees with weaker such mandates 9…”
Section: Yes—babak Javid Dirk Bassler Manuel B Bryantmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed reason for the observed differences is that the Sturgis Rally was associated with lower compliance with non-pharmaceutical interventions (NPIs), such as mask wearing and physical distancing, that are associated with decreased transmission risk. Observational data showed that attendees from regions with stricter NPI mandates were associated with lower onward transmission risk than attendees with weaker such mandates 9…”
Section: Yes—babak Javid Dirk Bassler Manuel B Bryantmentioning
confidence: 99%
“…At the time, many experts and pundits warned that such protests may fuel large transmission clusters for covid-19, but these fears were not realised 8. By contrast, the mass outdoor Sturgis Motorcycle Rally in South Dakota, USA, is considered to have been the trigger for a huge superspreading-type event that resulted in a devastating chain of covid-19 transmission and disease 9. One proposed reason for the observed differences is that the Sturgis Rally was associated with lower compliance with non-pharmaceutical interventions (NPIs), such as mask wearing and physical distancing, that are associated with decreased transmission risk.…”
Section: Yes—babak Javid Dirk Bassler Manuel B Bryantmentioning
confidence: 99%
“…Endogeneity may, however, persist if policy stringency levels and protests are correlated for other reasons. For instance, the level of policy stringency might be shaped by previous protests when they acted as super spreaders (see Dave et al 2020aDave et al , 2020bDave et al , 2020cDave et al , 2021. To further address these concerns, we test if trends in the outcome variable (probability of protests) before the outbreak of the COVID-19 pandemic are parallel across different levels of exposure to the treatment (different levels of policy stringency and different levels of inequality).…”
Section: Endogeneitymentioning
confidence: 99%
“…For the present study, we employed convenience sampling to rapidly ascertain and summarize the impact of the announcement of the nation’s first SIPO on March 16, 2020. More specifically, we use a difference-in-differences estimator to estimate changes among respondents living in the seven counties in the San Francisco Bay Area affected by the announcement versus those living elsewhere in the U.S. A large body of COVID-19 literature has employed quasi-experimental methods to examine the impact of the pandemic on a variety of topics including superspreader events [ 21 23 ], air pollution [ 24 , 25 ], unemployment [ 26 ], and demand for online shopping [ 27 ]. Many of these quasi-experimental studies have focused on changes in human mobility using aggregated smartphone-based measures such as time spent at home [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%